ADULT ONSET STILL DISEASE - Faruk Şendur,; Gülcan Gürer,; Ali Aydeniz, (Archives of Rheumatology, 2004)
Adult onset Still's disease (ASD) is a systemic inflammatory disorder of unknown etiology and pathogenesis. It is suggested that infectious agents and genetical factors may play a role in etiology of the disease. A few diagnostic criteria was developed in order to make diagnosis of ASD. NSAID, corticosteroids and immun-modüled drugs are used for it's treatment. In this review, current literatures about ASD are overviewed and briefly summarized.